Diseño de un curso virtual dirigido a los docentes de la unidad educativa Lauro Damerval Ayora N° 1, para la inclusión de las tic en la planificación curricular de la asignatura de ciencias naturales, como aporte al proceso de enseñanza aprendizaje de los estudiantes del sexto grado de educación general básica, periodo lectivo 2014-2015 - Quishpe Solano, Carmen Yomari (2016)
The performed thesis work was focused on the needs and requirements of “Lauro Damerval Ayora” N° 1 Educational Unit, where it was evidenced that the main problem of the institution was the lack of inclusion of Information and Communication Technology (ICT) in the curriculum planning of teachers, problem originate by the lack of knowledge and training that teachers received about how to employ them in the education. For that reason it was proposed the development of an online course for teachers in order to promote the inclusion of ICT in micro curricular planning with teachers of sixth- grade of Basic General Education. For the thesis elaboration it was used the ADDIE methodology, because it is a flexible and systemic model employed in educational contexts, which allowed proper and optimal development of the research. For the selection of themes to be included in the virtual course, it was applied a survey, which reflected that the main difficulties of the teachers was handling of basic tools of Microsoft Office package, organization of information in the email and the development of computer games to employ during the class. The virtual course developed allowed the teachers to know the advantages that provide the inclusion of ICT in the micro curricular planning of Natural Science subject, at the same time awoke and promoted the interest in the teachers to learn to handle and use them within the teaching learning process of the students, which indicated that the developed work and the included contents were relevant and covered with the needs and requirements of the teachers